2001
DOI: 10.1002/nrc.10011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of brain‐derived neurotrophic factor in neural differentiation of mouse embryonic stem cells and neural precursor cells

Abstract: SUMMARY Embryonic stem (ES) cells, which have pluripotency in differentiation,have been considered as an excellent source for cell replacement therapy of damaged tissues. Although neurotrophic factors induce neural differentiation in neural precursor cells, their actions in ES cells are not clear. This study was designated to examine the effect of brain-derived neurotrophic factor (BDNF) on neural differentiation in mouse ES cells. Undifferentiated mouse ES cells were maintained at suspension culture in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…As described previously for MSCs or adult NSCs overexpressing untagged BDNF (Lim et al, 2011;Ma et al, 2012), or as revealed by application of BDNF to EBs (Kang et al, 2001) or to NSCs (Silva et al, 2009), neuronal differentiation of our BDNF-GFPoverexpressing ESCs was strongly enhanced (Figs 4,5). Given that this enhancement was critically dependent on the extracellular availability of BDNF (see inhibition by TrkB-Fc receptor bodies; Fig.…”
Section: Enhanced Neuronal Differentiation Of Bdnf-gfp Escssupporting
confidence: 62%
See 1 more Smart Citation
“…As described previously for MSCs or adult NSCs overexpressing untagged BDNF (Lim et al, 2011;Ma et al, 2012), or as revealed by application of BDNF to EBs (Kang et al, 2001) or to NSCs (Silva et al, 2009), neuronal differentiation of our BDNF-GFPoverexpressing ESCs was strongly enhanced (Figs 4,5). Given that this enhancement was critically dependent on the extracellular availability of BDNF (see inhibition by TrkB-Fc receptor bodies; Fig.…”
Section: Enhanced Neuronal Differentiation Of Bdnf-gfp Escssupporting
confidence: 62%
“…Furthermore, BDNF is known to support differentiation of embryonic, mesenchymal and neural stem cells into neurons in vitro and in vivo (Kang et al, 2001;Ortega and Alcántara, 2010;Trzaska and Rameshwar, 2011). For example, studies using embryonic and adult neuronal precursor cells from mouse striatum revealed a BDNF-mediated increase in neuron number and neurite outgrowth that was independent from increased cell division and increased survival (Ahmed et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that paracrine signaling via BDNF, but to a lesser extent BMP-2, secreted by ECs likely contributed to neurite elongation and activation of Ca 2+ oscillations. BDNF is a key growth factor that accelerates neuronal differentiation 39 by activation of MAPK/ERK and PI3K/Akt signaling pathways 40 . We, therefore, hypothesize that in co-culture with ECs, BDNF and potentially BMP-2 secreted by ECs and present in the culture medium upregulated neuronal differentiation and survival of neurons through autocrine signaling in co-culture system.…”
Section: Resultsmentioning
confidence: 99%
“…Our data provide evidence for BDNF-induced NPC differentiation into both favored lineages in vivo, leading to cell replacement of damaged neurons and oligodendrocytes. We and others have already shown that BDNF enhances neuronal differentiation, as it is known to support differentiation of embryonic, mesenchymal, and NSCs into neurons in vitro and in vivo [ 8 10 , 19 ]. Furthermore, BDNF is important for oligodendroglial proliferation, differentiation, and myelination [ 11 13 ].…”
Section: Discussionmentioning
confidence: 99%